MicroRNAs in Esophageal Adenocarcinoma: Functional Significance and Potential for the Development of New Molecular Disease Markers - V. Bobryshev, Yuri; N. Orekhov, Alexander; A. Chistiakov, Dmitry (Current Pharmaceutical Design, 2015)
Esophageal adenocarcinoma (EAC) originates from the neoplastic changes in the esophageal epithelium. Barrett’s esophagus (BE) precedes EAC. In BE metaplasia, the normal stratified squamous epithelium is replaced by the intestinal columnar epithelium. Esophageal metaplasia might further progress to dysplasia, neoplasia, and EAC. The neoplastic progression from BE to EAC is accompanied with marked histological and molecular changes including deregulation of key signaling pathways and expression of various genes including microRNA (miRNA). To date, stable and progressive changes in expression levels of different miRNA subsets are shown for each stage of EAC carcinogenesis. This suggests that miRNAs might become promising markers for BE/EAC diagnosis and prognosis of survival of EAC patients and lymph node tumor metastases. Development of new molecular markers based on the assessment of miRNAs circulating in patients’ biofluids would improve the effectiveness and cost-effectiveness of esophageal cancer surveillance regimens and open new possibilities for high throughput screening programs to identify BE patients who are at high-risk for the development of highgrade dysplasia or progression to EAC.
Keywords: Barrett’s esophagus